Analisis penentuan kurs valuta asing di Indonesia - Josephine Wuri (Economic Journal of Emerging Markets, 2001)
This research is intended to analyze the effect of money supply, real income and interest rate in Indonesia and in the United States on the determination of the exchange rate. In addition, this study also wishes to determine appropriate model of exchange rate in Indonesia.